2008
DOI: 10.1038/jhh.2008.129
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lowering blood pressure by magnesium supplementation in diabetic hypertensive adults with low serum magnesium levels: a randomized, double-blind, placebo-controlled clinical trial

Abstract: To test the blood pressure (BP)-lowering effect of oral magnesium supplementation (that is, magnesium chloride (MgCl 2 ) solution) in diabetic hypertensive adults with hypomagnesaemia not on diuretic treatment but receiving concurrent captopril, we conducted a double-blind, placebo-controlled trial. Eighty-two subjects between 40 and 75 years of age were randomly enrolled. Over 4 months, subjects in the intervention group received 2.5 g of MgCl 2 (50 ml of a solution containing 50 g of MgCl 2 per 1000 ml of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 38 publications
2
74
1
3
Order By: Relevance
“…Although some cohort studies have found lack of association between dietary magnesium intake and the risk of hypertension, there has been recent interest in magnesium therapy as a method to reduce blood pressure. However, clinical evidence for blood pressure reduction with magnesium supplementation remains equally unclear [24][25][26]. A recent meta-analysis of 22 clinical trials suggests a negative association between magnesium supplementation and diastolic and systolic blood pressure; these trials found an average reduction of 2-3 mmHg for diastolic blood pressure and 3-4 mmHg for systolic blood pressure [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some cohort studies have found lack of association between dietary magnesium intake and the risk of hypertension, there has been recent interest in magnesium therapy as a method to reduce blood pressure. However, clinical evidence for blood pressure reduction with magnesium supplementation remains equally unclear [24][25][26]. A recent meta-analysis of 22 clinical trials suggests a negative association between magnesium supplementation and diastolic and systolic blood pressure; these trials found an average reduction of 2-3 mmHg for diastolic blood pressure and 3-4 mmHg for systolic blood pressure [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, prospective cohort studies have also found weak [20,21] or no relationships [22,23] between Mg and the development of hypertension. Clinical findings on this topic are mixed, including reports that Mg supplementation lowers [24][25][26] or does not affect [27] BP.…”
Section: Introductionmentioning
confidence: 99%
“…21 Most of the trials required that hypertensive patients go off medications ≥1 month (22 of 34 trials); and patients in 4 trials were still taking medications during the trials. [22][23][24][25] Additionally, 2 trials included participants with low serum Mg (<0.74 mmol/L). 25,26 BPs were generally measured by sphygmomanometer (14 trials) or automatic monitor (9 trials), and only 2 trials applied ambulatory monitor recording of 24-hour BPs.…”
Section: Characteristics Of Included Trials and Participantsmentioning
confidence: 99%
“…[22][23][24][25] Additionally, 2 trials included participants with low serum Mg (<0.74 mmol/L). 25,26 BPs were generally measured by sphygmomanometer (14 trials) or automatic monitor (9 trials), and only 2 trials applied ambulatory monitor recording of 24-hour BPs. 27,28 The trial durations varied from 3 weeks to 6 months, although the vast majority (30 of 33 trials) were longer than 1 month.…”
Section: Characteristics Of Included Trials and Participantsmentioning
confidence: 99%
“…Magnesium is also effective in further reducing BP in stage I hypertension, diabetes mellitus, and pregnancy, when coadministered with antihypertensive agents such as angiotensin-converting enzyme inhibitors (ACEI), angiotensin receptor blockers (ARBs), calcium-channel blockers (CCBs) diuretics, beta-blockers (BB), methyldopa, and other pharmacological agents [30][31][32][33] . A comprehensive analytical review of 44 human studies of oral magnesium for hypertension showed that Mg supplements enhance BP-lowering effect of antihypertensive medications [ 31 ] .…”
Section: Effect Of Magnesium On Bpmentioning
confidence: 99%